The Absentee’s Woman (Novel): A Semiotic study - kamel, Ishraq (Al-Adab Journal, 2019)
The semiotic trend of recent critique took a wide range of interest by critics and readers alike, especially after the widespread that it witnessed upon publishing the work of Grimace and its applicability to literary and non-literary texts. This has widened the circle of interest, and thus we chose the novel ‘The Absentee’s Women’ by the Iraqi novelist Mahdi Essa Alsaqr to be a sample for applying the study, which takes the semiotic approach through the use of the procedural mechanisms of Paris School of Semiotics and the critique viewpoint of its founder Grimas. This study starts with an introduction that gives a background for semiotics and its impact on critique to clarify some of certain issues such as the disagreement among critics about its origins definition. Then, the study is divided into three sections: the rhetorical level, the narrative level and depth level. Then comes the conclusion that is about the most important outcome of the study. Finally, we have a list of sources and references.